I and II Workshops about Probiotics, Prebiotics and Simbiotics for Animal and Human Health - Pérez Bueno, Tania; Fortes Ferreira, Célia L.; Sánchez Miranda, Lilian; Carneiro, Heloisa; Vega Cañizares, Ernesto; Díaz Casaña, Elaine; Diniz, Damiana; Hernández Delgado, Silvia (Revista de Salud Animal, 2014)
With the participation of Cuban and Brazilian specialists, the I and II Workshops of Functional Foods: impacts of the use of probiotics, prebiotics and simbiotics for animal and human health were held. The I meeting was held on November 15th, 2013 at CENSA, Cuba, and the II one on April 4th, 2014 at UFV, Brazil. The working group was composed by experts from different scientific centers. In Cuba the Cuban Research Institute of Sugar Cane Derivatives (ICIDCA), the Institute of Animal Science (ICA), the Institute of Food and Drugs (IFAL) and the Center of Genetic Engineering and Biotechnology (CIGB), and in Brazil the National Center for Research on Dairy Cattle (CNPGL) belong to Brazilian Agricultural Research Corporation (EMBRAPA). These seminars were developed based on the International Cooperation Agreement between Brazil and Cuba (Capes/MES-Cuba) and brought representatives from various teams to present and discuss different aspects concerning the design, mechanisms of action, production and use of probiotics, prebiotics and simbiotics in animal and human health, in order to conduct researches to obtain functional foods for the welfare of populations.